Whole genome sequencing of a novel carrageenan-degrading bacterium Photobacterium rosenbergii and oligosaccharide preparation - Chen, Jing; Chen, Runmin; Cheong, Kit-Leong; Wang, Zhuo; Li, Rui; Jia, Xuejing; Zhao, Qiaoli; Liu, Xiaofei; Song, Bingbing; Zhong, Saiyi (Frontiers in Microbiology, 2025)
IntroductionCarrageenan oligosaccharides are of significant interest due to their diverse bioactivities, necessitating efficient methods for their production. To this day, the discovery and isolation of microorganisms capable of effectively degrading carrageenan is still crucial for the production of carrageenan oligosaccharides. In addition, there are no current reports of bacteria of the genus Photobacterium capable of secreting κ-carrageenanase or degrading carrageenan.MethodsIn the current study, strain GDSX-4 was obtained from Gracilaria coronopifolia after enrichment culture, primary screening and rescreening and was initially characterized by morphology and 16SrDNA. The pure culture of strain GDSX-4 was further subjected to bacterial genome sequencing assembly and bioinformatic analysis. Specifically, homology group cluster (COG) annotation, CAZy (carbohydrate-active enzyme) database annotation and CAZyme genome clusters (CGCs) annotation were utilized to identify potential polysaccharide degradation functions. Enzymatic activity was assessed under different conditions, including substrate, temperature, pH, and the presence of metal ions. Hydrolysis products were analyzed using thin-layer chromatography (TLC) and electrospray ionization mass spectrometry (ESI-MS).ResultsPhotobacterium rosenbergii GDSX-4 is a Gram-negative bacterium isolated from the red algae, capable of degrading several polysaccharides. The draft genome was predicted to have 6,407,375 bp, 47.55% G+C content and 6,749 genes. Among them, 214 genes encoding carbohydrate enzymes were annotated, including carrageenase, agarose, alginate lyase, and chitinase. GDSX-4 exhibited remarkable carrageenan-degrading activity, with a specific enzyme activity of 46.94 U/mg. Optimal hydrolysis conditions were determined to be 40°C and pH 7.0, with the enzyme retaining 80% of its activity below 30°C and across a pH range of 4.0–10.0. Metal ions such as as K+, Na+, and Ba2+ enhanced enzymatic activity, while Ni2+, Mn2+, and Cu2+ had inhibitory effects. kappa-carrageenan was totally hydrolyzed into oligosaccharides with degrees of polymerization ranging from 2 to 6.DiscussionThese findings highlight the potential of GDSX-4 for the efficient production of carrageenan oligosaccharides, paving the way for applications in the food and agricultural industries. Future studies may focus on the efficient expression of κ-carrageenase and expand its industrial application in the preparation of oligosaccharides.